2016
DOI: 10.1007/s40620-016-0306-5
|View full text |Cite
|
Sign up to set email alerts
|

The extra-phosphate intestinal load from medications: is it a real concern?

Abstract: Our results suggest that the prevalence of phosphate-containing medications is quite low and it is possible to identify, within each drug category, the medications containing P as an excipient. Calcium phosphate, the most prevalent form, has a lower rate of intestinal absorption than sodium phosphate salts. We did not measure the actual P content, but existing data (measured or estimated) show that it is generally low, except for a few medications that can be easily identified. Thus, the extra-phosphate load f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This is further complicated by other hidden sources of phosphorus in foods and medications (see Box 3). [23][24][25][26][27] In the United States, the recommended daily allowance of phosphorus for adults is 900 mg/day. In a typical diet, the phosphorus content is generally proportional to the amount of protein, and the 3 main sources of phosphorus are proteins, dairy products, and cereals and grains.…”
Section: Box 2 Novel Paradigm For Hyperphosphatemia Management In Ckmentioning
confidence: 99%
See 1 more Smart Citation
“…This is further complicated by other hidden sources of phosphorus in foods and medications (see Box 3). [23][24][25][26][27] In the United States, the recommended daily allowance of phosphorus for adults is 900 mg/day. In a typical diet, the phosphorus content is generally proportional to the amount of protein, and the 3 main sources of phosphorus are proteins, dairy products, and cereals and grains.…”
Section: Box 2 Novel Paradigm For Hyperphosphatemia Management In Ckmentioning
confidence: 99%
“…More than 10% of drug formulations contain phosphorus, which can significantly contribute to the daily phosphorus intake in patients taking multiple medications simultaneously. 26,27 Common medications high in phosphorus include: 1. Paroxetine (antidepressant) 2.…”
Section: Box 3 Hidden Sources Of Phosphorusmentioning
confidence: 99%
“…Furthermore, recent studies have shown that the current food tables do not take additives into account, and that phosphate and potassium content of processed foods may be significantly higher. Moreover, added phosphate or potassium are rapidly bioavailable and potentially more toxic [16][17][18][19][20].…”
Section: Lipidsmentioning
confidence: 99%
“…It is mostly used as a pharmaceutical excipient, which in most cases is reported on the packaging label without the precise concentration 33 . Phosphates as excipients are most commonly used as diluents, buffers to prevent pH fluctuations, and provide the required density for the preparation, thereby facilitating appropriate route of administration 32,36 . Although excipients are often considered as pharmacologically inert ingredients, they could also have iatrogenic effects as shown by diethylene glycol in sulfanilamide, which caused acute kidney injury, killing more than 100 people in the US 37 .…”
Section: Phosphorus Content In Ckd Medicationmentioning
confidence: 99%
“…Commonly used drugs for long-term oral administration in patients with CKD alleviate comorbidities related to CV system and central nervous system (CNS). The different medications include antihypertensives, anticoagulants, immunosuppressants, hypoglycemic agents, lipid-lowering drugs, analgesics, antihistamines, antidepressants, anti-gout drugs, and gastrointestinal drugs 35,36 . A potential confounder in estimating the medicinal phosphorus content is the wide variation observed with different formulations of the same drug from different manufactures, which has been highlighted in previous studies 31,35 .…”
Section: Phosphorus Content In Ckd Medicationmentioning
confidence: 99%